2019
DOI: 10.3389/fmicb.2019.00098
|View full text |Cite
|
Sign up to set email alerts
|

Plant Root Exudates Are Involved in Bacillus cereus AR156 Mediated Biocontrol Against Ralstonia solanacearum

Abstract: The biological control process mediated by microbes relies on multiple interactions among plants, pathogens and biocontrol agents (BCAs). One such efficient BCA is Bacillus cereus AR156, a bacterial strain that controls a broad spectrum of plant diseases and potentially works as a microbe elicitor of plant immune reactions. It remains unclear, however, whether the interaction between plants and B. cereus AR156 may facilitate composition changes of plant root exudates and whether these changes directly affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 50 publications
0
44
0
1
Order By: Relevance
“…Specifically, Wang et al. (2019) reported that B. cereus AR156 can induce the secretion of organic acids, including lactic acid and caproic acid, from tomato roots, thereby promoting the growth and metabolism of root‐dwelling microorganisms. It suggested an important method that bacteria employ to improve their viability in barren soil, while consequently promoting soil organic matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Wang et al. (2019) reported that B. cereus AR156 can induce the secretion of organic acids, including lactic acid and caproic acid, from tomato roots, thereby promoting the growth and metabolism of root‐dwelling microorganisms. It suggested an important method that bacteria employ to improve their viability in barren soil, while consequently promoting soil organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Secretions of B. cereus AR156 are able to influence plant root secrets (Zhou et al., 2016). The change of root secrets has effects on plant growth; moreover, it provides more organic matter, such as lactic acid and caproic acid, for the soil (Wang et al., 2019). It has also been shown that PGPR are able to promote soil water retention (Zheng et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to too little fengycin being secreted by IMA 8 under the same conditions, although few studies display that iturin and fengycin produced by B. amyloliquefaciens have high activity against R. solanacearum [46,47], and purified fengycin has stronger antibacterial activity than iturin [47]. By comparison, no lipopeptides are found in strains IMA 4, IMA 7 and IMA 11 except IMA4 but they also show higher disease control efficacy, possibly being associated with mechanisms of induced resistance [33,48].…”
Section: Discussionmentioning
confidence: 99%
“…In an endophytic strain of Enterobacter, Taghavi et al [73] observed the expression of genes related to the synthesis of antimicrobial compounds, such as 4-hydroxybenzoate and 2-phenylethanol, which may protect the plant from attack by both fungi and bacteria. In the specific case of Bacillus, a number of studies have indicated that this bacterium may facilitate alterations in the composition of the exudates of the roots, which may have a direct effect on the growth of pathogens [74]. However, extracellular polysaccharides, known as Microbe-Associated Molecular Patterns (MAMPs) [75], may be involved in the biocontrol processes of B. cereus.…”
Section: Discussionmentioning
confidence: 99%